2021
DOI: 10.1039/d1dt01810h
|View full text |Cite
|
Sign up to set email alerts
|

Assembling γ-graphyne surrounding TiO2 nanotube arrays: an efficient p–n heterojunction for boosting photoelectrochemical water splitting

Abstract: Photoelectrochemical water splitting is an excellent strategy for hydrogen generation, and it is pivotal to develop photoanodes with proficient sunlight harvesting, rapid charge separation, and enhanced electron injection efficiency. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Regarding PEC OER enhancement using metal-free secondary semiconductors, Qiu et al recently reported construction of p-n heterojunctions by functionalization of TiO 2 nanotube arrays with γ-graphyne nanosheets (Figure 11d). [69] It can be seen that the addition of γ-graphyne increased the photocurrent density of the TiO 2 nanotube arrays (0.44 mA cm− 2 ), with 0.3-graphyne/TiO 2 (0.75 mA cm −2 ) having the optimal γ-graphyne loading (Figure 11e). The enhanced PEC performance was attributed to good band alignment between TiO 2 and γ-graphyne for charge separation, as well as more efficient light absorption (Figure 11f).…”
Section: Tio 2 -Based Heterojunction Nanoarraysmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding PEC OER enhancement using metal-free secondary semiconductors, Qiu et al recently reported construction of p-n heterojunctions by functionalization of TiO 2 nanotube arrays with γ-graphyne nanosheets (Figure 11d). [69] It can be seen that the addition of γ-graphyne increased the photocurrent density of the TiO 2 nanotube arrays (0.44 mA cm− 2 ), with 0.3-graphyne/TiO 2 (0.75 mA cm −2 ) having the optimal γ-graphyne loading (Figure 11e). The enhanced PEC performance was attributed to good band alignment between TiO 2 and γ-graphyne for charge separation, as well as more efficient light absorption (Figure 11f).…”
Section: Tio 2 -Based Heterojunction Nanoarraysmentioning
confidence: 96%
“…[57] This issue can be alleviated in semiconductor heterojunction systems, as the built-in electric field at the heterogeneous interface enables efficient charge carrier separation. [91] To this end, many narrow bandgap semiconductors, such as In 2 S 3 (2.1 eV), [57] Cu 2 O (2.17 eV), [53,80] Fe 2 O 3 (2.2 eV), [68] CeO 2 (2.4 eV), [46] CdS (2.42 eV), [70,73,74,92] graphyne (2.65 eV), [69] ZnSe (2.6 eV), [78] C 3 N 4 (2.7 eV) [48,61,79,93] and PbTiO 3 (2.75 eV), [76] have been hybridized with TiO 2 , leading to large enhancements in PEC OER performance.…”
Section: Tio 2 -Based Heterojunction Nanoarraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Qiu et al. assembled γ‐graphyne surrounding TiO 2 nanotube arrays with an efficient p‐n heterojunction for boosting photoelectrochemical water splitting [155] . Moreover, graphene quantum dots (GQDs) with sizes of less than 10 nm can behave as a photosensitizer donating electrons to the CB of TiO 2 (Figure 13a–b) [156,157] …”
Section: Figurementioning
confidence: 99%
“…[154] Very recently, Qiu et al assembled γgraphyne surrounding TiO 2 nanotube arrays with an efficient pn heterojunction for boosting photoelectrochemical water splitting. [155] Moreover, graphene quantum dots (GQDs) with sizes of less than 10 nm can behave as a photosensitizer donating electrons to the CB of TiO 2 (Figure 13a-b). [156,157] On the other hand, heterostructures of TiO 2 with other graphene-like 2D materials are also intensively studied, especial for 2D transition metal dichalcogenides (TMDs) such as MoS 2 and MoSe 2 .…”
Section: Homo/heterostructures With Perfect Band Matchingmentioning
confidence: 99%